PERANTI KOHESI DALAM WACANA TULIS SISWA: PERKEMBANGAN DAN KESALAHANNYA - Syamsul Ghufron (Fakultas Sastra Universitas Negeri Malang, 2012)
The aim of the study was to describe the cohesive devices found in the students’ written discourse along with its development and usage errors. The data were gathered from the students’ writing products from 3rd, 4th, and 5th graders of SDN Baratajaya, Surabaya by using observation and tests as the instruments to obtain the data. The result of the study shows that allelementary students’ written discourses (grade 3, 4 and 5) apply the cohesive devices. The cohesive devices most widely used in their written discourse are conjunctions, lexical synonymy, and grammatical ellipsis. The findings illustrate not only the development of the usage on cohesive devices through its percentages on conjuctions, repetition, and synonymy in the students’ written discourses but also the description of the cohesive device errors through the use of conjunction, ellipsis,substitution, reference and repetition.